2018
DOI: 10.1103/physreva.97.050302
|View full text |Cite
|
Sign up to set email alerts
|

Entangled states in the role of witnesses

Abstract: Quantum entanglement lies at the heart of quantum mechanics and quantum information processing. In this work, we show a new framework where entangled states play the role of witnesses. We extend the notion of entanglement witnesses, developing a hierarchy of witnesses for classes of observables. This hierarchy captures the fact that entangled states act as witnesses for detecting entanglement witnesses and separable states act as witnesses for the set of non-block-positive Hermitian operators. Indeed, more hie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…A framework which assembles hierarchies of “witnesses” has been proposed in [ 42 ]. In this framework, a coherence witness can witness coherent states, and on the other hand, a coherent state can also act as a “high-level-witness ” of coherence witnesses which witnesses coherence witnesses.…”
Section: Common Coherent Statesmentioning
confidence: 99%
“…A framework which assembles hierarchies of “witnesses” has been proposed in [ 42 ]. In this framework, a coherence witness can witness coherent states, and on the other hand, a coherent state can also act as a “high-level-witness ” of coherence witnesses which witnesses coherence witnesses.…”
Section: Common Coherent Statesmentioning
confidence: 99%
“…They showed that an arbitrary quantum state ρ can always be written in a form as ρ = λρ BSA +(1−λ)ρ OptE , where ρ BSA is a separable state and the weight λ of the separable part is maximal. Later, the form was proven to be unique [7,8]. The separable state ρ BSA is called the BSA of ρ, and the convex decomposition is called the BSA decomposition (also called Lewenstein-Sanpera decomposition).…”
mentioning
confidence: 99%
“…The separable state ρ BSA is called the BSA of ρ, and the convex decomposition is called the BSA decomposition (also called Lewenstein-Sanpera decomposition). Recently, Wang showed a framework where entangled states play the role of high-level witnesses [8,9]. Instead of using a numerical value [10], Wang characterized the entanglement of an entangled state ρ using a set of entanglement witnesses for detecting the entangled state D ρ = {W |tr(W ρ) < 0}, where W is the entanglement witness of ρ.…”
mentioning
confidence: 99%
See 2 more Smart Citations